Mercury contamination in fanned fish setup on former garimpo mining areas in the Northern Mato Grosso State, Amazonian region, Brazil - Farias, R. A.; Hacon, S.; Campos, R. C.; Argento, R. (Elsevier B.V., 2005)
The garimpo gold mining activity has released about 2.500 tons of mercury in the Brazilian Amazonian environment in the 1980-1995 period. The northern region of Mato Grosso State, an important gold mining and trading area during the Arnazonian gold rush is now at a turning point regarding its economic future. Nowadays, the activities related to gold mining have only a low relevance on its economy. Thus, the local communities are looking for economic alternatives for the development of the region. Cooperative fish farming is one of such alternatives. However, some projects are directly implemented on areas degraded by the former garimpo activity and the mercury left behind still poses risks, especially by its potential accumulation in fish. The objective of the present study was to evaluate the levels of mercury contamination in two fish farming areas, Paranaita and Alta Floresta, with and without records of past gold-washing activity, respectively. Data such as mercury concentration in fish of different trophic level, size, and weight as well as the water physical and chemical parameters were measured and considered. These preliminary data have shown no significant difference between these two fish fanning areas, relatively to mercury levels in fish. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: mercury; fish fanning; gold mining areas; Amazonian region